O papel das redes de transformação no processo de inovação: estudos de caso sobre a descoberta e a comercialização da inovação - Vitoreli, Marinez Cristina [UNESP]; Gobbo Junior, Jose Alcides [UNESP] (Associação Brasileira de Engenharia de Produção, 2013)
Innovation is widely recognized as important. In addition, in this context, innovation networks have gained importance in academic studies, since an organization alone, does not always have access to all necessary resources. Gobbo Junior and Olsson (2010) proposed a model of network innovation whereby the transformation networks would be the linking structures between exploration and exploitation networks. In this context, this paper presents two case studies of innovation networks, aiming to increase the understanding on transformation networks. The objective was to understand how they interconnect exploration and exploitation networks; the main actors present in this interface; and to evaluate whether these actors can act as agents, to accelerate the innovation process. It was possible to verify how the transformation networks interconnect exploration and exploitation, and identify the practices and their main actors.

A importância da inovação é algo reconhecido. Nesse contexto, as redes de inovação ganham importância nos estudos acadêmicos, uma vez que uma organização, isoladamente, nem sempre tem acesso a todos os recursos necessários. Gobbo Junior e Olsson (2010) apresentam um modelo de inovação em rede segundo o qual as redes de transformação seriam as estruturas presentes entre as de exploração e aplicação. Nesse contexto, este artigo apresenta dois estudos de caso de inovação em redes, tendo como objetivo aumentar a compreensão sobre as redes de transformação. Busca-se entender como elas interligam as redes de exploração e aplicação, os principais atores presentes nessa interface e avaliar se esses atores podem atuar como agentes aceleradores do processo de inovação. Foi possível verificar como as redes de transformação interligam as redes de exploração e aplicação, bem como identificar suas práticas e principais atores.
The role of transformation networks in the process of innovation: case studies on the discovery and commercialization of innovation
Keywords: Inovação; Teoria de redes; Redes de exploração e aplicação; Modelos de inovação em rede; Innovation; Network theory; Exploration and exploitation networks; Models of innovation in networks